Pengembangan Bahan Ajar Pendidikan Kesehatan melalui Media Powerpoint Interaktif Pembelajaran PJOK Sekolah Menengah Pertama - Subekti, Radik; Raharjo, Hermawan Pamot (Universitas Negeri Semarang, 2023)
The purpose of this study was to produce a product for developing health education teaching materials through interactive media learning PJOK for Junior High Schools. This research is a development research or R&D which refers to the development of Borg & Gall. The data from the validation of learning experts got a percentage of 94% in the